Respon Antera Anthurium andreanum Linden ex André cv. Carnaval pada Medium dengan Berbagai Kombinasi Konsentrasi Zat Pengatur Tumbuh - Budi Winarto; Nurhayati A. Mattjik (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2009)
Anther culture is one of technological breakthrough in producing homozygous lines, which is an important genetic resource in plant breeding programs. Response of anther in various regeneration media is one of important basic information in developing anther culture method. The objective of this research was to investigate callus formation and evaluate the potential of using this cultivar in developing anther culture of anthurium. Anthers, yellow and reddish callus derived from anther culture of A. andreanum cv. Carnaval were used in the study. Eight regeneration media i.e. MMS + (1) 0.5 mg/l TDZ + 0.01 mg/l NAA,( 2) 0.5 mg/l TDZ + 0.05 mg/l NAA, (3) 1.0 mg/l TDZ + 0.01 mg/l NAA, (4) 1.5 mg/l TDZ + 0.02 mg/l NAA, (5) 1.0 mg/l 2,4-D + 1.5 mg/l TDZ + 0.01 mg/l NAA,(6) 0.75 mg/l 2,4-D + 2.0 mg/l TDZ + 0.05 mg/l NAA, (7) 0.75 mg/l 2,4-D + 1.0 mg/l TDZ + 1.0 mg/l BAP + 0.01 mg/l NAA, and (8) 0.25 mg/l 2,4-D + 1.5 mg/l TDZ + 0.75 mg/l BAP +0.02 mg/l NAA for yellow and reddish callus were investigated in this research. Factorial experiment was arranged in randomized complete block design with four replications. Results of this study indicated that callus formation was startedat ± 2.7 month after culture and observable by 3.5 month after culture. Average number of callus per anther was 3.6 per replication. Reddish callus grew faster than the yellow one. The callus cultured in MMS with 0.02 mg/l NAA gave high results of shoot initiation time , number of shoots primordia per explant, and average height of shoot primordial i.e. 8.5week, 10.8, and 0.78 cm respectively. Keywords: Anther culture, callus formation and regeneration, and medium